2013
DOI: 10.17265/1934-8975/2013.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Weibull Statistics in Dielectric Strength of Oil-impregnated Pressboard under Ramped AC and DC Voltages

Abstract: AC and DC breakdown tests were performed on large populations of oil-impregnated pressboard samples. The effect of voltage ramp rate on dielectric strength has been investigated. A statistical analysis of breakdown data was carried out using the Weibull distribution. The 90% confidence intervals of Weibull graphs were calculated. The study shows that dielectric strength and shape parameter change versus ramp rate. The variations are attributed to the size and number of defects. Discharges occur from the oil to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A conductive path is formed in the process, which has been observed to degrade the insulation system. It has been reported that the resistance of oil-impregnated pressboards to DC voltage is superior to that of AC voltage, according to a reliability analysis based on step voltage practices [ 9 ]. The modelling of lightning strikes in transformers was undertaken by Florkowski and et al They discovered that the strength of the windings is influenced by the waveform of the applied voltage and the standard voltage pulse used.…”
Section: Introductionmentioning
confidence: 99%
“…A conductive path is formed in the process, which has been observed to degrade the insulation system. It has been reported that the resistance of oil-impregnated pressboards to DC voltage is superior to that of AC voltage, according to a reliability analysis based on step voltage practices [ 9 ]. The modelling of lightning strikes in transformers was undertaken by Florkowski and et al They discovered that the strength of the windings is influenced by the waveform of the applied voltage and the standard voltage pulse used.…”
Section: Introductionmentioning
confidence: 99%